Design and experimental study of a planetary gearing mechanism based on twice unequal amplitude transmission ratio - Liu, Jiangang; Yu, Gaohong; Tong, Zhipeng; Hua, Yao (International Journal of Agricultural and Biological Engineering, 2022)
To obtain the optimal seedling taking trajectory, this study proposed the adjustment of the total transmission ratio curve by using human-computer interaction. On the basis of this design method, a planetary non-circular gear mechanism was designed that can realize the twice unequal amplitude transmission ratio to meet the seedling harvesting requirements. The cubic non-uniform B-spline curve was used to fit the twice unequal amplitude transmission ratio curve, and the transmission ratio was freely distributed in two levels. The seedling pick-up mechanism was designed by controlling the seedling taking track and the corresponding attitude directly through the local section of the total transmission ratio, and the gear pitch curve was directly controlled by the transmission ratio. The kinematics model of the seedling pick-up mechanism was also established. Furthermore, the influence of the total transmission ratio on the seedling picking track, the ratio of the wave crest to the amplitude, and the mechanism parameters were discussed. A human-computer interactive optimization software was developed using Matlab, and a set of optimal parameters for the seedling pick-up mechanism was obtained to meet the transplanting requirements. By using the Adams software, the virtual prototype simulation of the seedling pick-up mechanism was completed, and the idle experiment for the track and attitude of the prototype was conducted through high-speed camera technology. The theoretical, simulated, and experimental trajectories were consistent with each other. Results revealed that the success rate of the seedling picking exceeded 90% when the rotation speeds were 40 r/min, 50 r/min, and 60 r/min, and the qualified rate of the matrix decreased with the increase in rotating speed. Moreover, the number of damaged plants increased with the increase in rotating speed. The experimental results showed that the seedling pick-up mechanism designed using the proposed method demonstrated a good effect and met the required seedling picking performance. Keywords: seedling pick-up mechanism, second unequal amplitude, planetary gear train, seedling picking experiment DOI: 10.25165/j.ijabe.20221501.6168 Citation: Liu J G, Yu G H, Tong Z P, Hua Y. Design and experimental study of a planetary gearing mechanism based on twice unequal amplitude transmission ratio. Int J Agric & Biol Eng, 2022; 15(1): 155–163.